A four-leg voltage source inverter fed asymmetrical two-phase induction motor drives - Y. Kumsuwan (2018)
In this paper, a four-leg voltage source inverter is proposed the variable voltages variable frequency of the asymmetrical two-phase induction motor drives. The novel method is based on de-couple control of the auxiliary and main windings of the orthogonal reference two-phase voltages in generating three-level sinusoidal pulsewidth modulation output voltage for the asymmetrical two-phase induction motor. The simulation and experimental results are illustrated in this paper confirming that the capability of the proposed system such as torque and speed responses, motor winding current distortion both in dynamic and steady state with load variation, torque-speed characteristic, and simple algorithm.